2019
DOI: 10.22201/fe.01851667p.2019.308.69625
|View full text |Cite
|
Sign up to set email alerts
|

Ecowas Common Currency: How Prepared Are Its Members?

Abstract: <p align="center"><strong>ABSTRACT</strong></p><p>This study operationalizes the Optimum Currency Area (OCA) to investigate the preparedness of Economic Community of West African States (ECOWAS) members to form a Monetary Union (MU). Inflation and output models are estimated, with the sample 1988:01 to 2017:12 for the former and 1967 to 2016 for the latter. Analyses of ECOWAS convergence criteria, impulse responses, variance decompositions and correlations of shocks of these two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…100 For instance, the Economic Community of West African States (ECOWAS), at the end of its July 2009 Summit in Abuja, announced the decision to adopt the ECO as a single currency for the regionan initiative that has been seen as a milestone towards concretizing the AfCFTA. 101 In a political ploy, and with the complicity of France, the eight francophone ECOWAS countries proceeded prematurely in December 2019 to announce a rebranding of the CFA Franc to henceforth be called the ECO. 102 France followed through with new legislation in May 2020 purportedly ending its fiscal hegemony over the eight ECOWAS francophone countries, a move which Kamga finds unconvincing, in the sense that convertibility of the ECO would remain guaranteed by France and pegged to the Euro at the same rate that the CFA Franc is pegged to the Euro.…”
Section: Capitalist Problem Matrix Of Economic Interest and The Ineptitude Of African Governmentsmentioning
confidence: 99%
“…100 For instance, the Economic Community of West African States (ECOWAS), at the end of its July 2009 Summit in Abuja, announced the decision to adopt the ECO as a single currency for the regionan initiative that has been seen as a milestone towards concretizing the AfCFTA. 101 In a political ploy, and with the complicity of France, the eight francophone ECOWAS countries proceeded prematurely in December 2019 to announce a rebranding of the CFA Franc to henceforth be called the ECO. 102 France followed through with new legislation in May 2020 purportedly ending its fiscal hegemony over the eight ECOWAS francophone countries, a move which Kamga finds unconvincing, in the sense that convertibility of the ECO would remain guaranteed by France and pegged to the Euro at the same rate that the CFA Franc is pegged to the Euro.…”
Section: Capitalist Problem Matrix Of Economic Interest and The Ineptitude Of African Governmentsmentioning
confidence: 99%
“…Several studies have shown the weak or negative correlation of macroeconomic shocks affecting ECOWAS countries (Houssa, 2008;Mati et al, 2019;Debrun et al, 2005). However, these studies analyze the effects of shocks on each economy.…”
Section: Economic and Monetary Integration In Ecowasmentioning
confidence: 99%
“…For automatic economic stabilisers, they are almost non-existent. Real business cycle amongst member countries ECOWAS (Mati et al. , 2019) and amongst the WAMZ countries (Houssa, 2018) have also been found to be asymmetric.…”
Section: Introductionmentioning
confidence: 99%